Design and Synthesis of Some New Thiazolo[3,2-b]-l,2,4-triazole-5(6H)-ones Substituted with Flurbiprofen as Anti-inflammatory and Analgesic Agents - Doğdaş, Emine; Tozkoparan, Birsen; Kaynak, Filiz Betül; Eriksson, Lars; Küpeli, Esra; Yeşilada, Erdem; Ertan, Mevlüt (Arzneimittelforschung, 2007)
In the course of our ongoing studies, a series of thiazolo[3,2-b]-1,2,4-triazole-5(6H) -ones substituted with flurbiprofen (CAS 5104-49-4) has been prepared. The compounds were synthesized by the cycliza-tion of the 3-[(2-fluoro-4-biphenyl)ethyl]-5-mercapto-l,2,4-triazole (3) with chloro-acetic acid and relevant benzaldehydes in the presence of acetic acid, acetic anhydride and anhydrous sodium acetate in one step. The product of this one-pot synthesis that precipitated on cooling of the reaction mixture was identified undoubtedly by X-ray crystallographic analysis as thiazolo [3,2-b]-1,2,4-triazole. In-vivo anti-inflammatory and analgesic activities of the compounds were assessed by carrageenan-induced hind paw edema and p-benzoquinone-induced abdominal constriction tests in mice, respectively. In addition, the ulcerogenic risks were evaluated. It is worthy of saying that the compounds which maintained analgesic/anti-inflammatory activity of the starting compound were found to be safer with regard to gastric lesion risks at 100 mg/kg oral dose when compared with flurbiprofen. Among the synthesized compounds 3d showed the highest analgesic and antiinflammatory activity without inducing any gastric lesion and deserves further attention in order to develop new lead drug candidates.
Keywords: Anti-inflammatory and analgesic activity; Anti-inflammatory drugs, non-steroidal; CAS 5104-49-4; Flurbiprofen; Thiazolo[3,2-b]-l,2,4-triazole-5(6H)-ones, synthesis, X-ray crystallographic analysis